Near-infrared Integral-field Spectroscopy of the Wind Forming Region of CW Leo - Hyosun Kim; Youichi Ohyama; Ho-Gyu Lee; Ji Hoon Kim (The Astronomical Journal)
The circumstellar envelope of the carbon star CW Leo exhibited various unexpected changes in recent optical imaging observations. We have performed a follow-up observation using the Near-infrared Integral-Field Spectrograph (NIFS) equipped on the Gemini-North telescope. We report the near-infrared counterparts of a local brightness peak in the optical at the stellar position of CW Leo. On the other hand, a second peak detected at short wavelengths in the J band coincides with the brightest, bluest position in the optical images. The absorption features in the K band are minimized at a radius of 0 $\mathop{.}\limits^{{\rm{^{′} }}{\rm{^{′} }}}$ 2 from the predicted stellar position. The reduction of the absorption depths likely indicates dilution of the absorption features by thermal emission of dust grains newly formed at such a radius and heated by radiation from the central star. The broad absorption feature at 1.53 μ m is significantly deeper than in template carbon stars, consistent with the presence of a substantial amount of circumstellar material around CW Leo. Its northeastern quadrant lacks circumstellar absorption features and scattered light in the near-infrared regime, which are possibly manifestations of its conical cavity in both gas and dust. In addition, a cross correlation of CO overtone bands indicates that the average expansion velocity of dust grains is smaller to the northern direction, likewise the velocity of transverse wind components derived using the differential proper motion of a circumstellar whirled pattern. The gradual brightening of CW Leo and the changes in its innermost circumstellar envelope need further continuous monitoring observations to properly understand its transitional phase toward the post-asymptotic-giant-branch stage.